Effect of Season, Position of Node and Growth Regulating Substances on Adventitious Root Induction in an Edible Bamboo, Dendrocalamus brandish (Munro) Kurz. - Raveendran, V. P.; Seethalakshmi, K. K.; Jijeesh, C. M. (Indian Forester, 2010)
Dendrocalamus brandisii is a large size sympodial edible bamboo species of India and Myanmar with multifarious uses. A study was conducted to find out the effect of three seasons - summer, rainy and winter and three different positions of culmbase, middle and top and five different concentrations of two growth regulating substances - NAA and IBA on adventitious root induction in this species. Factor analysis of the observations revealed the significant influence of interaction effects (P=0.01) of season, position and growth regulating substance on growth attributes like height and collar girth of the sprouts, rooting percentage, number of roots and length of the longest root. Out of the three seasons, summer season and of the three positions, basal portion gave maximum rooting. Application of growth regulating substances increased the number of roots. Clustering of different treatment combinations identified the cuttings collected in summer season from basal portion of the culms treated with IBA 200 ppm as the superior treatment.